Bipyridyl– and pyridylquinolyl–phenothiazine structures as potential photoactive ligands: Syntheses and complexation to palladium. Issue 32 (9th August 2017) - Tabey, Alexis; Mendy, Jonathan; Hermange, Philippe; Fouquet, Eric
Graphical abstract: Highlights: Easy to-synthesize bipyridyl– and pyridylquinolyl–phenothiazine structures. Ligand complexation to Pd(OAc)2 and UV–visible absorption studied. Molecular modeling suggesting intramolecular electronic transfers upon irradiation. Potential photo-electronically tunable ligands. Abstract: Three new bipyridyl– and pyridylquinolyl–phenothiazine structures were synthesized through Pd-catalyzed C–N couplings between phenothiazine and the corresponding bromo-heteroaryls. For the 2-( N -phenothiazine)-bipyridine, boat conformation was determined for the phenothiazine moiety by X-ray diffraction analysis. Single well-defined palladium acetate complexes were observed by 1 H NMR analysis with the 4-( N -phenothiazine)-bipyridine and the pyridyl-5-( N -phenothiazine)-quinoline. Compared to the naked ligands, the UV–visible absorption spectra showed, in these cases, significantly red shifted λmax upon coordination. Preliminary modeling experiments with the free and the coordinated 4-( N -phenothiazine)-bipyridine suggested for both the occurrence of electronic transfers from the phenothiazine to the bipyridine. Potentially enabling the tuning of the electron density of the coordinating moiety upon near-UV irradiation, this bipyridyl–phenothiazine structure could be the origin of a novel class of photo-active ligands for applications in organometallic catalysis.